PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PADA KANTOR BPKAD KABUPATEN BOJONEGORO - CHRISTANTO, FEBRYAN (Jurnal Ilmu Manajemen (JIM), 2017)
Goals to be achieved in this research is to determine and analyze the variables of leadership and organizational culture are simultaneously significant effect on employee satisfaction and want to know and analyze the variables of leadership and organizational culture is partially significant effect on employee satisfaction and wanted to know which of the above variables dominant influence on employee satisfaction Agency for Financial Management and Asset Bojonegoro. The theoretical basis used that every organization has a culture, each different from one another. Organizational culture, in addition to the ability to integrate the daily activities of employees to achieve the planned objectives, it can also help organizations to adapt well to the external environment for rapid and appropriate response. Categories leaders there are as a function of interpersonal, informational functions and decision-making functions. For a leader to function by using its influence to motivate and encourage employees to achieve organizational goals. Model analysis of data using multiple linear regression. This model was chosen to investigate the relationship between the dependent variable with the independent variable and determine how much influence the independent variable (X) on the dependent variable (Y) either partially or influence together. Keywords: Organizational Culture, Leadership,BPKAD Bojonegoro